Hydrogen sulfide can inhibit and enhance oxygenic photosynthesis in a cyanobacterium from sulfidic springs. (4th March 2015) - Klatt, Judith M.; Haas, Sebastian; Yilmaz, Pelin; de Beer, Dirk; Polerecky, Lubos
Summary We used microsensors to investigate the combinatory effect of hydrogen sulfide (H2S) and light on oxygenic photosynthesis in biofilms formed by a cyanobacterium from sulfidic springs. We found that photosynthesis was both positively and negatively affected by H2S: (i) H2S accelerated the recovery of photosynthesis after prolonged exposure to darkness and anoxia. We suggest that this is possibly due to regulatory effects of H2S on photosystem I components and/or on the Calvin cycle. (ii) H2S concentrations of up to 210 μM temporarily enhanced the photosynthetic rates at low irradiance. Modelling showed that this enhancement is plausibly based on changes in the light‐harvesting efficiency. (iii) Above a certain light‐dependent concentration threshold H2S also acted as an inhibitor. Intriguingly, this inhibition was not instant but occurred only after a specific time interval that decreased with increasing light intensity. That photosynthesis is most sensitive to inhibition at high light intensities suggests that H2S inactivates an intermediate of the oxygen evolving complex that accumulates with increasing light intensity. We discuss the implications of these three effects of H2S in the context of cyanobacterial photosynthesis under conditions with diurnally fluctuating light and H2S concentrations, such as those occurring in microbial mats and biofilms.